The impact of environmental factors on the speed of events regarding maturity in schoolgirls from Cambé, Paraná, Brazil - Sérgio Zucas; Enio Ronque; Edilson Cyrino; Antonio Simões; Helio Serassuelo Júnior; Sérgio Parra (Universidade Federal de Santa Catarina, 2006)
The purpose of this study was to analyze the impact of socioeconomic and cultural indicators on the pace of maturity. The sample consisted of 163 schoolgirls (11-12 year old) from Cambé, Paraná, Brazil. Cultural and socioeconomic variables were collected by using social inventories, while maturity status was measured according to Tanner method (1962) adapted by Bonjardim and Hegg (1988). The findings showed that higher socioeconomic level groups (A and B) presented lower pace of maturity status (p < 0.05). Despite the fact that there was not a general tendency, the results suggest a clear interference of the environment and it may be linked to several factors, especially that girl's needs for having a role within her family and even her own heredity. RESUMO O propósito deste estudo foi analisar o impacto de alguns indicadores socioeconômicos e culturais sobre a velocidade dos eventos maturacionais. Fizeram parte da amostra 163 escolares (11-12 anos), do sexo feminino, do município de Cambe, Paraná, Brasil. A caracterização cultural e socioeconômica foi realizada por meio de inventários sociais, ao passo que a análise maturacional seguiu os critérios propostos por Tanner (1962) e adaptados por Bonjardim e Hegg (1988). Os achados demonstraram que os grupos economicamente superiores (A e B) tiveram uma menor velocidade no processo maturacional (P < 0,05). Estes resultados, apesar de não serem uma tendência geral, sugerem uma clara interferência do meio ambiente e podem estar associados a diversos fatores, dentre os quais se destaca a necessidade da jovem ocupar uma posição dentro da família ou, ainda, a própria hereditariedade.